2004
DOI: 10.1128/ec.3.1.212-220.2004
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Evidence for Interaction between η- and β-Tubulins

Abstract: The thermosensitive allelic mutations sm19-1 and sm19-2 of Paramecium tetraurelia cause defective basal body duplication: growth at the nonpermissive temperature yields smaller and smaller cells with fewer and fewer basal bodies. Complementation cloning of the SM19 gene identified a new tubulin, eta-tubulin, showing low homology with each of the other five tubulins, ␣ to , characterized in P. tetraurelia. In order to analyze -tubulin functions, we used a genetic approach to identify interacting molecules. Amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…In addition, basal body duplication is impaired after ε-tubulin depletion [ 20 ]. A mutation found in sm19 , encoding the rare eta now called ζ [ 21 ], was reported to inhibit basal body duplication and to induce the delocalization of γ-tubulin [ 22 , 23 ].…”
Section: Basic Basal Body Structurementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, basal body duplication is impaired after ε-tubulin depletion [ 20 ]. A mutation found in sm19 , encoding the rare eta now called ζ [ 21 ], was reported to inhibit basal body duplication and to induce the delocalization of γ-tubulin [ 22 , 23 ].…”
Section: Basic Basal Body Structurementioning
confidence: 99%
“…The mutations in the gene encoding this protein caused an inhibition of basal body duplication [ 42 ]. Further physiological and genetical studies indicate an interaction with microtubules [ 22 ]. In a recent functional study of ζ-tubulin in Xenopus [ 21 ], no evident basal body defect was observed, leading to the conclusion that ζ-tubulin is involved in basal body orientation and distribution and might function by interacting with other tubulins.…”
Section: Notable Basal Body Findingsmentioning
confidence: 99%
“…Finally, forward genetic strategies identified a Paramecium ‐specific tubulin superfamily member, η‐tubulin that was originally found as a conditional mutation ( sm19 ) that, at restrictive temperature, inhibited basal body duplication (85). η‐Tubulin is a divergent tubulin that genetically interacts with β‐tubulin in a manner suggesting that the proteins directly interact (86). Furthermore, γ‐tubulin is mislocalized in η‐tubulin mutants (85).…”
Section: Ciliatesmentioning
confidence: 99%
“…For example, in T. thermophila GFP-BTU2 is found in somatic cilia and BBs, whereas GFP-BLT1 and GFP-BLT4 are observed in macronucleus MT arrays and in the mitotic spindle of the micronucleus (Pucciarelli et al, 2012). In Paramecium the tubulin gene family possesses two α- and three β-tubulin genes (Dupuis, 1992; Dupuis-Williams et al, 1996; Ruiz et al, 2004).…”
Section: Introduction: the Complex Architecture Of A Single Cell Orgamentioning
confidence: 99%